Influence of Dehydration Temperature and Time on Physicochemical Properties of Tomato (Solanum lycopersicum L.) Powder - Degwale, Alemu; Asrat, Fentahun; Eniyew, Kefale; Asres, Derajew; Tesfa, Tiru; Ayalew, Asrat (Frontiers in Sustainable Food Systems, 2022)
The purpose of this research was to determine the optimum dehydration temperature and time length for a better physicochemical quality of tomato powders. The treatments consisted of 70, 80 and 90°C dehydration temperatures and 9, 11, and 13 h time durations arranged in a completely randomized design (CRD) with triplicates. The inlet and outlet air temperatures of the hot air oven dryer were about 24 and 60°C respectively with an air velocity of about 2.9 m/s. Fresh tomatoes were used as a control. It has been observed that the major quality parameters of tomato powders were significantly increased with increasing dehydration temperature and time up to 80°C and 11 h respectively. When the dehydration temperature and time length went beyond 80°C and 11 h respectively, the quality of tomato powders declined. The maximum TSS content (7.433 °Brix), titratable acidity (0.4967), rehydration ratio (3.437), lycopene content (0.4512 mg/100 g) and lower pH value (4.433) were obtained at 80°C temperature and 11 h dehydration time. Moisture content was reduced to 11% at the same dehydration temperature and time length without considerable physiochemical quality loss. Inversely, vitamin C was reduced as dehydration temperature and time increased. Generally, the results of this study showed that dehydration of tomatoes with 80°C and 11 h temperature and time length respectively, provides better physicochemical quality of tomato powders. Future research is suggested on consumers' acceptance of dehydrated tomato powders.